721. Clinical Respiratory Syndromes and Association with Influenza Clinical Diagnostic Testing and Antiviral Treatment among Children Hospitalized with Acute Respiratory Illness, 2015–2016. (26th November 2018) - Campbell, Angela P; Rha, Brian; Ogokeh, Constance; Englund, Janet; Halasa, Natasha B; Selvarangan, Rangaraj; Staat, Mary A; Weinberg, Geoffrey A; Azimi, Parvin H; Boom, Julie A; McNeal, Monica; Sahni, Leila C; et al.
Abstract: Background: We investigated clinical influenza testing and treatment in children hospitalized with acute respiratory illness (ARI) who had distinct respiratory syndromes. Methods: Children <18 years old with ARI were enrolled at seven hospitals in the New Vaccine Surveillance Network (NVSN) between November 1, 2015–June 30, 2016. ICD10 admission diagnosis codes were grouped to define syndromes of bronchiolitis, asthma, pneumonia, and croup. At clinician discretion, influenza testing with a rapid influenza diagnostic test or molecular assay was performed on respiratory samples. As part of the study, each site performed influenza testing using molecular assays on mid-turbinate nasal and throat swabs from all enrolled children. Analysis was restricted to influenza season; children who received antivirals before hospitalization were excluded. Results: Among 2, 134 children with available ICD10 codes, on preliminary analysis 1, 119 (52%) had influenza testing ordered by a clinician: 111 (10%) were positive, and 57 (51%) of 111 received antiviral treatment. Of the 2, 134, 858 (40%) had one of the four mutually exclusive syndromes (table). Hospital clinical testing per clinician discretion was influenza positive in 16 of the 858 children (percent positivity per syndrome ranged from <1% to 38%; table). Research study testing of children not undergoing clinical influenza testing identified 11 additional positives. Antiviral treatment was highest for pneumonia patients. Conclusion: Understanding testing and treatment practices by clinical syndrome may help to identify missed opportunities for influenza diagnosis and treatment. Table: Disclosures: J. Englund, Gilead: Consultant and Investigator, Consulting fee and Research support. Novavax: Investigator, Research support. GlaxoSmithKline: Investigator, Research support. Alios: Investigator, Research support. MedImmune: Investigator, Research support. N. B. Halasa, sanofi pasteur: Investigator, Research support. GSK: Consultant, Consulting fee. Moderna: Consultant, Consulting fee.